Clinical and psychological manifestations of psychological disagaptation in perticipants of battle actions with visual body injuries: results of screening examination - Abdryakhymov, R. (Journal of Education, Health and Sport, 2018)
The objective: to evaluate screening assessment of clinical and psychological manifestations of psychological maladaptation in combatants with injuries of visual organ and optimize measures of their medical and psychological support. Under the conditions of PIC, 91 combatants were examined, 49 had eye trauma and partial vision loss due to psychological maladaptation; in 42 persons they observed the psychological maladaptation. All the persons under examinations were screened for their mental status using the clinical diagnostic scale CAPS (Clinical-Administered PTSD Scale) and a questionnaire for determining the level of neuroticism and psychopathy (LNP). The use of neuroticism and psychopathisation questionnaire for screening research with a view to determine the signs of psychological maladaptation in combatants including those with vision trauma fully meets the objectives of the study. Neuroticism and psychopathisation levels determined, clearly demonstrate the shift of psychological maladaptation. The results of CAPS scale use for screening of post-traumatic stress disorder in the persons under examination makes it possible to suspect these shifts. To interpret the results obtained it is necessary to make a comparison with the data of clinical and diagnostic examinations. Further investigations should be directed to the development of maladaptative persons psychological state detailed study.